2017
DOI: 10.1111/jocn.13999
|View full text |Cite
|
Sign up to set email alerts
|

The intersection of culture in the provision of dementia care: A systematic review

Abstract: Open access education and training to support communication is required, alongside the development of robust interventions to support the process of acculturation of migrant healthcare professionals and care workers to provide culturally competent person-centred dementia care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 52 publications
(146 reference statements)
0
11
0
Order By: Relevance
“…Although there is an expectation that staff working in New Zealand hospitals attained a minimum IELTS score of 7.0, there always remains the possibility that questions posed, as they are in the ADQ, were misunderstood. Also cultural values in regard to people with dementia vary across cultures (Brooke, Cronin, Stiell, & Ojo, 2017). For example, in the context of the US study – set in care home facilities (Zimmerman et al., 2005) – it was shown that Black and other minority staff were less likely than Whites to report person-centred care.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is an expectation that staff working in New Zealand hospitals attained a minimum IELTS score of 7.0, there always remains the possibility that questions posed, as they are in the ADQ, were misunderstood. Also cultural values in regard to people with dementia vary across cultures (Brooke, Cronin, Stiell, & Ojo, 2017). For example, in the context of the US study – set in care home facilities (Zimmerman et al., 2005) – it was shown that Black and other minority staff were less likely than Whites to report person-centred care.…”
Section: Discussionmentioning
confidence: 99%
“…The Workgroup recommends a personcentred, cultural competency framework [45] that addresses: (1) experiences of persons living with dementia and caregivers; (2) their lived environment; and (3) their socio-cultural context. The sociocultural context includes attitudes, values, beliefs, and behaviours of cultures, as well as how these intersect with age, race, ethnicity, gender/gender identity, sexual orientation, and relationship to persons living with dementia, as well as account for educational background, social class, linguistics, religion, and other social and behavioural determinants of health [46,47].…”
Section: Summit Third Theme: Technology Evidence-based Practices Culturally Competent Carementioning
confidence: 99%
“…Ageism can be overcome by understanding the different cultures of older people, how care is provided and ageing perceived. With particular reference to older person care and dementia the provision of culturally appropriate person-centred care has been identified as essential (Brooke et al 2017).…”
Section: Attitudes Predict Behaviourmentioning
confidence: 99%